The Geogebra Learning Media for Students' Mathematical Problem Solving Ability - Munawwarah, Wa Ode Shofiatul; Saleh; Salim (Jurnal Amal Pendidikan, 2024)
The low mathematical problem-solving ability of students and technological advances became the beginning of this research, with the aim of finding out the influence of geogebra  learning media for students' problem-solving ability. A quasi-experiment design was employed, specifically a Post-Test Only Control Group design. The population of this research is all 10th grade students, with classes X.1 and X.2 selected as the sample. Data were collected through observation sheets and tests of mathematical problem-solving skills. The collected data were analyzed both descriptively and inferentially. Descriptive analysis showed that the average mathematical problem-solving ability of students taught using GeoGebra media was 80.185, with 44.44% rated as very good, 37.04% as good, and 18.52% as adequate. In contrast, the average problem-solving ability of students taught without GeoGebra media was 72, with 28% rated as very good, 28% as good, 28% as adequate, and 16% as poor. Inferential analysis yielded a . Based on these results, it can be concluded that there is a significant influence of the GeoGebra learning media for students’ mathematical problem solving ability